PERAN GURU DALAM MEMBENTUK KARAKTER DISIPLIN SISWA PASCA COVID-19 DI SMAN 20 SURABAYA - Sahrul, Muhammad; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2023)
Online to offline learning in the post-pandemic period has resulted in a decrease in the character of discipline in students. This has caused teachers to think about how to shape students' disciplinary character during post-pandemic learning and what problems teachers face in shaping students' disciplinary character. In the world of education, the teacher is a figure who has an important role in guiding and educating students to have commendable character. The role of teachers in shaping students' disciplinary character in the post-Covid-19 pandemic at SMAN 20 Surabaya teachers have roles such as teachers as demonstrators, teachers as class managers, teachers as facilitators and mediators, as well as teachers as evaluators. Teachers also have solutions to the problems faced during the post-pandemic period. In school education, there are character values that are considered important to support learning activities, namely discipline. The method used in the research is descriptive qualitative. The location of this object is SMAN 20 Surabaya. Data collection techniques using observation and interviews data analysis conducted in this study using the analysis method according to Miles and Huberman, which includes data reduction, data display, and data verification. The results of this study show how teachers play a role in shaping students' disciplinary character in post-Covid-19 and the problems faced by teachers. This has a solution provided by the teacher in shaping the character of discipline.